Balochistan : Architecture, Craft, and Religious Symbolism - Keiany, Mohesn (Karachi Oxford University Press, 2015)
This work discusses the interrelated dynamics of schooling, society and inclusive education, focusing on the knowledge and skills Teacher Education students need to make sense of their professional and social environment and to engage with the realities of schooling in South Africa and Africa.
Include Illustration, Bibliography and Index
Keywords: Teachers--Training of -- Inclusive education -- South Africa